Presence of Lamin A is Required for GATA3 and ERα Downregulation by Histone Deacetylase Inhibitor in Breast Cancer Cells - CAPO-CHICHI, D. CALLINICE (My University, 2018)
Breast cancer treatment is challenging due to the inconsistence in tumour biomarker expression including progesterone receptor (PR), estrogen receptor-α (ERα) and GATA3 transcription factor. GATA3 has role in epithelial cell differentiation along with nuclear envelope protein lamin A. The breast cancer cell line MCF7 expresses ERα, abnormal GATA3 isoforms, low PR but lacks lamin A. MCF7 cells are resistant to tamoxifen targeting ERα and more anticancer drugs are being studied to kill them. One of the mechanisms surrounding breast cancer initiation is histone deacetylation. Our objective is to investigate the effect of histone deacetylase inhibitor (HDACI) on PR, ERα and GATA3 expression along with the induction of apoptosis in MCF7 cells forced expressing lamin A. Subsequently, they are also explored as biomarkers for breast cancer prognostic and indicators for targeted breast cancer therapy. Methods: The HDACI used here is Suberoyl-Bis-Hydroxamic Acid (SBHA). Western blot was used to analyze the expression of PR, ERα, and GATA3 in MCF7 control transfected with histone H2B-GFP (MCF7-H2B-GFP) and in MCF7 transfected with lamin A-RFP (MCF7-LA-RFP). The analyses were carried out before and after treatment with DMSO (mock) or SBHA (1 or 2 µM) for 12h. The in vivo expression of the PR, ERα and GATA3 were also explored in 36 archived cell lysates derived from breast cancer micro-biopsies. Results: MCF7-H2B-GFP treated with SBHA increased PR, ERα while MCF7-LA-RFP treated with SBHA reduced ERα and GATA3 but not PR. Biomarkers analysis in ductal carcinoma micro-biopsies derived samples showed that 30% had lost lamin A while 64% expressed PR, ERα and GATA3. Conclusion: In presence of lamin A, SBHA downregulated cancer initiators GATA3 and ERα while inducing cell death. These biomarkers could be useful molecular tools prior to initiating targeted breast cancer therapy.
Keywords: Suberoyl-Bis-Hydroxamic Acid; GATA3; ERα; targeted breast cancer therapy